Syntactical Development on Second Language Writing: A Case of L2 Child Learner on Immersion Experience Abroad - Hanna Sundari; Rina Husnaini Febriyanti (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Development of child language is tremendously complex, remarkable and wondrous. In a second language acquisition context, a child can acquire his second language in either acquiring both languages at the same time or learning the second language after mastering the first one. This present research is concerned to describe the syntactical development particularly for second language writing of an eight-year old child who has experienced immersion abroad for one year in L2-speaking country. The participant is an eight-year old child from Jakarta Indonesia who has experienced immersion environment in Australia for one year. The research will be carried out qualitative naturalistic research design. Not less than 38 documents of participant’s paperwork during her school year were then collected, grouped and analysed. From the findings, it is known that morphological processes on L2 such as affixes and verb changes have emerged. Meanwhile, the findings also show the development on morphemic, phrasal and sentential level on acquiring L2. Some morphemes have been acquired such as the suffix, the changing of verb, the -ing form. Moreover, post-noun prepositional phrases are the most emerged phrases. On sentential level, active declarative sentences are the most frequently appeared. However, some errors and inconsistency also occur indicating the development of her second language.